Rapid Hybridoma Screening Method for the Identification of Monoclonal Antibodies to Low-Abundance Cytoplasmic Proteins - L.A. O’Reilly; L. Cullen; K. Moriishi; L. O’Connor; D.C.S. Huang; A. Strasser (BioTechniques)
Screening assays are the most time-consuming and labor-intensive part of generating monoclonal antibodies (MAbs). Antibodies identified by enzyme-linked immunosorbent assay (ELISA) screening often are not suitable for their intended application such as immunofluorescence staining. We describe here a rapid and efficient flow cytometric screening procedure for the identification of MAbs directed against low-abundance cytoplasmic proteins, in our case, the pro-apoptotic molecule Bim. Cells from an equal mixture of a parental cell line and a subline expressing Bim were fixed, permeabilized and incubated with hybridoma supernatants. The supernatants were derived from a fusion of Sp2/0 plasmacytoma cells and spleen cells from a rat immunized with recombinant glutathione-S-transferase (GST)-BimL fusion protein. Secondary staining with fluorochrome-labeled anti-rat Ig antibodies allowed detection of clones expressing Bimspecific antibodies. The screening procedure was rapid and efficient, and most monoclonal antibodies identified were proven to be useful for immunofluorescence staining and other applications.